Fundamental understanding on low-friction mechanisms at amorphous carbon interface from reactive molecular dynamics simulation - Li, Xiaowei; Wang, Aiying; Lee, Kwang-Ryeol (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Amorphous carbon (a-C) film arouses enormous interest in both scientific and engineering communities because of its excellent anti-friction property. However, due to the complexity of working conditions and the lack of in-situ characterization technique into sliding interface, the direct comparison between two widely accepted low-friction postulations, including the graphitization and passivation mechanisms, has never been performed experimentally. Herein, using reactive molecular dynamics simulation, we comparatively investigated the friction property and structural information of contacting interface under different passivated or graphitized states. For the passivation mechanism, the low friction behavior attributes to the reduction of both the real contact area and shearing strength of sliding interface due to the passivation of a-C dangling bonds. This is different from the graphitization mechanism, which improves the friction property by decreasing the shearing strength only. However, the graphitization mechanism strongly depends on the size and layer number of graphitized structure, causing the transition of sliding interface from a-C/a-C, a-C/G to G/G, which is followed by the low-friction mechanism evolved from passivation, synergistic effect between graphitization and passivation to graphitization mechanism. These disclose the fundamental understanding of friction-reducing mechanism and guide the design of a-C films and the development of related technologies for tribological applications. (C) 2020 Elsevier Ltd. All rights reserved.